Hydrogeological Criteria to Improve the Sponge City Strategy of China - Jin, Mengxiao; Lancia, Michele; Tian, Yong; Viaroli, Stefano; Andrews, Charles; Liu, Junguo; Zheng, Chunmiao (Frontiers in Environmental Science, 2021)
China is facing frequent waterlogging and an increasing water scarcity that mirrors the fast urban and economic expansion of the last 4 decades. To mitigate these issues, the government promulgated the “Sponge City” strategy; a concept rooted in practices in western countries aimed at collecting and reusing 65–90% of urban rainfall. The application consists of absorbent infrastructures such as green roofs and rain gardens combined with the pre-existing urban environment. However, due to climate heterogeneities and the different urbanization contexts in China, these goals may seem overly ambitious in many areas of the country. Compact urbanization, together with heavy rainfall concentrated in short events, puts dramatic stresses on these infrastructures. At the same time, overdesigned infrastructures are expensive and may not be practical to retrofit in existing urban areas. In this paper, the role of urban aquifers as natural Sponge City elements are investigated throughout China. The method of implementation is inexpensive and easy to apply, favoring the direct infiltration to the subsoil after the conversion of the urban surfaces from impervious to permeable. Infiltration to urban aquifers alleviates the pressure on sewers, urban streams, as well as waste-water treatment plants. Considering urban aquifers with different hydraulic characteristics, water table dynamics after large infiltration events from rainfall are simulated via numerical analysis. Hydrogeological and geomorphological analyses are carried out to individuate criteria for the mapping of high absorbance areas at the regional and local scales. A Sponge City approach involving the urban aquifers can represent a winning formula for the success of this ambitious but compelling plan.